Fuzzy (η,ϕ)-mixed Vector Equilibrium Problems - Salahuddin (Discontinuity, Nonlinearity, and Complexity, 2026)
In this research document, we study the fuzzy (η,ϕ)-mixed vector equilibrium problems. By using the concepts of KKM-mapping, we prove the existence theorem of fuzzy (η,ϕ)-mixed vector equilibrium problems.